Laplace, Hansen-Sargent and Beveridge-Nelson a note towards unified business application - Andric, Vladimir; Nenadovic, Sanja (Serbian Journal of Management, 2021)
The paper derives the equivalence condition between the Beveridge-Nelson decomposition and the Hansen-Sargent prediction formula in continuous time using Laplace transforms. The results presented show how the Hansen-Sargent prediction formula is relevant not just for present value discounting but also for the trend-cycle decomposition of cash flow streams in corporate finance.
Keywords: Beveridge-Nelson decomposition; Hansen-Sargent prediction formula; Laplace transforms; cash flows